An assessment of facilities and materials specification of residential buildings in Nigeria - Odediran, S.J.; Morakinyo, K.O.; Adeyinka, B.F. (Penerbit UKM, 2013)
The serviceability and comfortability of a building edifice are functions of its facilities and materials of construction. The level of facilities and quality of materials determine the degree of comfort, satisfaction and comfortability the users of residential buildings will enjoy. The study assessed the level of facilities and materials specification of residential buildings in Nigeria. Data were collected through questionnaire administered on the users of residential buildings in the study area. The study found out that the facilities available in most of the residential buildings are water closet and ceiling fan. Moreover, materials mostly used in construction were asbestos ceiling board, emulsion paint, floor screed among others. The study concluded that residential buildings in the study area were built with the basic facilities and materials for construction. The study therefore recommends the need for both the government and private players in housing to formulate policy to enforce a minimum standard of facilities and materials specification in residential buildings as essential need of man. This will eliminate the possibility of environmental challenges such as water and household-waste pollutions which could arise from non-availability of basic facilities and thereby improve the living conditions of the users.